Bioconversion of steviol glycosides into steviol by Microbacterium barkeri. Issue 11 (15th November 2021) - Jiang, Hui-Ling; Xuan, Yan; Zeng, Qian; Yu, Qi-Ming Jimmy; Zhang, Yu-Qian; Chen, Yu-Ru; Luo, Hai-Bo; Huang, He; Xu, Qing
Abstract: The strain which degraded steviol glycosides to steviol (STE) was screened and isolated from soil samples. A phylogenetic tree was constructed and used to determine the taxonomic status of the strain. 16S rDNA sequence was ultimately used to identify the strain as Microbacterium barkeri XJ. The transformation product was detected and identified as STE by HPLC/LC-MS/IR analysis. The bioconversion rate of 1% (v/v) steviol glycosides (stevioside, rebaudioside A, rebaudioside C) into STE in basic medium were 100% within 24 h, 84 h and 144 h, respectively. The results indicated XJ was more effective than mixed flora in the bioconversion of steviol glycosides to STE. Graphical Abstract: UF0001